Cellular benign fibrous histiocytoma in an 11-month-old child. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Fibrous histiocytoma of the skin is considered a benign tumor; however, in some cases it is characterized by local recurrences and sometimes metastases (2); most of these cases belong to the cellular variant. Cellular benign fibrous histiocytoma (CFH) usually appears in young adults, prefers the male sex and its most frequent location is the upper limb / shoulder girdle; its size usually does not exceed 2.5 cm; in 26% of cases CFH relapses locally (1). From a histological point of view one third of cases extends to the subcutaneous fat tissue and 12% of cases have foci of cellular necrosis; cell polymorphism is always present and the mitotic index is never high. The negativity of CD34 allows to exclude dermatofibrosarcoma protuberans, with which this tumor has sometimes been confused (1). The current case of CFH is therefore characterized by the early onset – third month – and by the considerable extension.